Monkeypox (MPOX)-Related Knowledge and Vaccination Hesitancy in Non-Endemic Countries: Concise Literature Review - Mohamed Lounis; Abanoub Riad (Vaccines, 2023)
In May 2022, the world witnessed the emergence of human monkeypox (MPOX), a new zoonotic viral disease in multiple non-endemic countries. This health threat has been associated with increased anxiety, especially after the COVID-19 catastrophe. In addition, people are exposed to an unprecedented amount of information, making them vulnerable to misinformation that may lead to embracing conspiracy theories. This literature review was conducted to evaluate the levels of MPOX-related knowledge and attitudes toward its vaccination by reviewing studies indexed in MEDLINE® until 15 November 2022. A total of 16 studies conducted in non-endemic countries were included in this review, predominantly in Europe, the Middle East, and Asia. Nine studies investigated exclusively MPOX-related knowledge and awareness, and two studies were exclusively related to MPOX vaccines, while five studies dealt with both topics. The target populations were mainly healthcare professionals and the general adult population. The results revealed an unsatisfactory level of knowledge and awareness among certain groups. Regarding vaccination, the results showed that vaccine hesitancy is still common for healthcare professionals except among Chinese healthcare professionals, where the rate of vaccine acceptance was estimated at 90.1%. This review could help understand the MPOX-related knowledge and awareness and vaccine hesitancy in the first months of the emergence of the MPOX by comparing their evolution in recent studies.